Female empowerment, cultural effects and savings: Empirical evidence from India - Ute Filipiak; Antonia Grohmann; Franziska Heyerhorst (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
This paper looks at household consumption and financial decisions made in a matrilineal society where women are by culture the financial household managers. This culture was strongly altered by the British in the mid-19th century in particular through christian missionaries who proclaimed that the role of the household manager is ascribed to men and not to women. Using two different datasets, our results show that female empowerment is stronger and individuals keep following the traditional matrilineal Khasi rules the further they live away from the former British base. Instrumental variable estimates exploiting differences in distance to the former British base in Cherrapunji, suggest that households where women are empowered, spend more on welfare enhancing goods such as education and nutrition, but are less likely to have savings left at the end of the month, and that these effects are causal.
Keywords: I3; O1; R20; Z1; 330; female empowerment; savings; India